Medidas de morbidade produzidas por duas fontes diversas: Ribeirão Preto, SP (Brasil), 1975 Morbidity statistics furnished by two different sources: Ribeirão Preto, SP (Brazil), 1975 - José da Rocha Carvalheiro; Clarisse Dulce Gardonyi Carvalheiro (Universidade de São Paulo, 1979)
Foram estudadas duas fontes de dados de morbidade: levantamento por entrevistas domiciliárias que corresponde a uma amostra representativa da cidade de Ribeirão Preto, e a morbidade em egressos hospitalares, produzida pelo Centro de Processamento de Dados Hospitalares do Departamento de Medicina Social da Faculdade de Medicina de Ribeirão Preto, USP, em 1975. Foram destacados 10 Grupos de Doenças da Classificação Internacional de Doenças (CID), Revisão de 1965. Em 1975, o número de hospitalizações de residentes foi de 1,1 por cem pessoas-mês. A morbidade proporcional dos vários grupos de doenças analisados mostrou, em ordem decrescente de freqüência nos egressos hospitalares, os Grupos da CID; VIII, VII, XVI, XVII, IX, X, I, XIII e V mais VI, sendo que os demais apresentam-se em pequena proporção. As entrevistas, mostraram: Grupos VIII, IX, V mais VI, XVI, XIII, VII, I, X, XVII e os demais em pequeno número. A ordenação dos diferentes grupos não é a mesma quando o diagnóstico é hospitalar ou resultante de entrevista domiciliária. A aplicação de um modelo ecológico clássico de atenção médica mostrou que, mensalmente, 608 pessoas adoecem, das quais apenas 11 são hospitalizadas. Morbidity statistics from two different sources are the subject of this report. The sources were a home interview survey of a representative sampling in the city of Ribeirão Preto and hospital in patient statistics furnished by the Hospital Data Processing Center of the Department of Social Medicine of the School of Medicine of Ribeirão Preto (University of S. Paulo) in 1975. Ten groups of diseases in the International Classification of Diseases (ICD), 1965 Revision, were focused on. The number of hospitalizations of city residents was 1.1 per 100 persons per month in 1975. Among hospital in patients, the incidence of morbidity of the ICD Groups analyzed was, in a decreasing order of frequency, as follows: VIII, VII, XVI, XVII, IX, X, I, XIII, and V plus VI. The other Groups are represented to a lesser degree. In the home interview survey, morbidity showed up in these ICD Groups: VIII, IX, V plus VI, XVI, XIII, VII, I, X, and XVII, with the other Groups presenting a lower rate of incidence. Clearly the order of the different groups is not the same when the diagnosis of morbidity is taken from hospital data files and from home interviews. The application of the classical ecological model of medical care shows that 608 persons feel sick per month, and, of these, only 11 are hospitalized.